Leadership And Cummunication Quality Affect Performance With Organizational Culture As An Intervening Variable - Fitria Marisya; Yohanes Susanto; Dwi Hanadya; Nyayu Ully Auliana; Marsinah Marsinah (Sekolah Tinggi Ekonomi dan Bisnis Syariah (STEBIS) Indo Global Mandiri, 2023)
This study examines the practice of human resources on leadership styles, communication, and performance of employees of local tax management agencies in Indonesia. This study also investigates the intervening role of organizational culture in the relationship between human resource practice, leadership style, communication, and employee performance of tax management agencies in Indonesia. This article has used a questionnaire to collect data and smart-PLS to examine the relationship between variables. The results show that the sub-structure equation shows that leadership and communication quality partially affect organizational culture, and in the leadership structure equation, communication quality and organizational culture have a positive effect on employee performance, but the leadership variable has a very dominant influence on local tax management agencies in Indonesia. Indonesia. The findings also show that organizational culture is a significantly strong intervening between leadership and communication quality on the performance of employees of local tax management agencies in Indonesia